Evaluation of the prevalence of asthma and chronic obstructive pulmonary disease among opium users, and cigarette smokers and comparison with normal population in Kharameh: a cross-sectional study - Raeisy, Laleh; Masoompour, Seyed Masoom; Rezaianzadeh, Abbas (BMC pulmonary medicine, 2023)
Background Recent studies have suggested that opium use may increase mortality from pulmonary diseases. However, there are limited comprehensive studies regarding the prevalence of Asthma and Chronic Obstructive Pulmonary Disease (COPD) among tobacco and opium users has been published. We aimed to determine the prevalence of respiratory disease among tobacco and opium users. Methods This cross-sectional study of tobacco and opium users and matched controls was conducted in the Kharameh Cohort, Fars, Iran. The prevalence of COPD and asthma, along with the participants demographical and spirometry data were examined. Results The average age of participants was 57 ± 8 years. Never smokers had a significant higher BMI (26.6 vs. 24.8), FEV1 (91% vs. 82%) and FVC (96% vs. 88%) values compared to participants with a positive smoking status. There was a statistical difference in the prevalence of COPD, asthma, and asthma COPD overlap (ACO) based on the participants smoking status, with the highest prevalence among opium and cigarette smokers, followed by opium users alone. Based on multivariate analysis, higher age, lower BMI, lower education than under diploma, cigarette smoking and opium use were significantly correlated with higher COPD prevalence; while lower age, cigarette smoking and opium use were significantly correlated with higher asthma prevalence. Illiterate participants had a significantly higher prevalence of COPD (23.6%), asthma (22%), and ACO (7.9%) among the educational groups. Regarding the prevalence of asthma, the higher socio-economic group had the lowest prevalence. Conclusions Opium and tobacco users had a significantly higher prevalence of respiratory diseases, along with lower lung function tests based on spirometry evaluation.